Analyzing the adoption of nutrition-sensitive carp-SIS polyculture technology: evidence from a case study in Bangladesh - Hossain, Nusrat Zaitun; Grote, Ulrike; Dubey, Sourabh Kumar (Frontiers in Sustainable Food Systems, 2024)
Introduction: Small indigenous species (SIS) of fish are rich in micronutrients that are essential to combat existing malnutrition in Bangladesh. However, their availability is constantly decreasing due to gradual environmental degradation making their availability irregular and hence expensive in market. Integrating SIS with carps in homestead ponds is being promoted as a form of nutrition-sensitive aquaculture to enhance both production and consumption of nutrient-rich species. Various IPMTs are suggested to boost nutrition-sensitive carp-SIS polyculture. Objectives: This study examines trends and factors influencing the adoption of IPMTs using the sustainable livelihood framework (SLF) approach. We address the following three key questions: (i) What are the trends in production and consumption of fish, in particular SIS from homestead ponds? (ii) Have farm households adopted or disadopted IPMTs over time? (iii) What are the determinants of adoption and disadoption of IPMTs? Methods: Based on primary data of 234 households from Barishal district from 2014 and 2022, we perform significance tests to compare project and non-project households in 2014 versus 2022 and apply fixed effects Poisson regression and fixed effects negative binomial regression models to identify household decisions to adopt IPMTs. Results and conclusion: Quantitative survey results indicate a significant increase in the production and consumption of SIS over time. In 2014, the project households exhibited adoption rates of 60% or more for various IPMTs such as stocking of fast-growing species, pre-stocking liming, pond dike construction, fertilizer application, stocking of high quality fish seeds, aquatic weed control, and turbidity management. However, by 2022, some of these IPMTs were disadopted by project households and only a few techniques, including providing sunlight exposure to ponds, pre-stocking liming, and supplementary feeding, were more widely used. Additionally, many non-project households also increased their adoption of IPMTs significantly. The fixed effects regression model shows that adoption is positively influenced by number of household members participating in aquaculture, size of the pond, sole ownership of the pond and number of years household has been involved in aquaculture. Follow-up activities such as monitoring and training of the project beneficiaries and government support are recommended to support long-term adoption of the IPMTs